Longitudinal evaluation of a household energy package on blood pressure, central hemodynamics, and arterial stiffness in China - Clark,SN; Schmidt,AM; Carter,EM; Schauer,JJ; Yang,X; Ezzati,M; Daskalopoulou,SS; Baumgartner,J (Environmental Research, 2019)
BackgroundCardiovascular diseases are the leading contributors to disease burden in China and globally, and household air pollution exposure is associated with risk of cardiovascular disease.ObjectivesWe evaluated whether subclinical cardiovascular outcomes in adult Chinese women would improve after distribution of an energy package comprised of a semi-gasifier cookstove, water heater, chimney, and supply of processed biomass fuel.MethodsWe enrolled 204 households (n=205 women) from 12 villages into a controlled before- and after-intervention study on cardiovascular health and air pollution in Sichuan Province. The intervention was distributed to 124 households during a government-sponsored rural energy demonstration program. The remaining 80 households received the package 18 months later at the end of the study, forming a comparison group. One woman from each household had their blood pressure (BP), central hemodynamics, and arterial stiffness measured along with exposures to air pollution and demographic and household characteristics, on up to five visits. We used a difference-in-differences mixed-effects regression approach with Bayesian inference to assess the impact of the energy package on sub-clinical cardiovascular outcomes.ResultsWomen who did not receive the energy package had greater mean decreases in brachial systolic (−4.1mmHg, 95% credible interval (95%CIe) −7.3, −0.9) and diastolic BP (−2.0mmHg, 95%CIe −3.6, −0.5) compared with women who received the package (systolic: −2.7, 95%CIe −5.0, −0.4; diastolic: −0.3, 95%CIe −1.4, 0.8) resulting in slightly positive but not statistically significant difference-in-differences effect estimates of 1.3mmHg (95%CIe −2.5, 5.2) and 1.7mmHg (95%CIe −0.3, 3.6), respectively. Similar trends were found for central BP, central pulse pressure, and arterial stiffness. Air pollution exposures decreased on average for both treatment groups